PENYIDIKAN TINDAK PIDANA TERHADAP PEMAKAI NARKOTIKA YANG DILAKUKAN OLEH ANAK DI KEPOLISIAN DAERAH RIAU - RENDI ARISANDI; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Children are the future generation, where the future of a nation looks, to children, because it’s so important for a child of nation. The Indonesian nation to make regulations o child protection regulated in law, number 22 of 2002 on the protection of children, until the chilo who commited a crime there are also laws that government law number 3 of 1997 on child’s justice. One example of case, children who commited the crime is Anggi Fernando and Wella Hasan, they are drug wers carried out by minors who were arrested by the police Riau area. Particulary the service unit direction of the regional police drug detective Riau. They were aristed by the police for being involved in cases at abuse narcotics. Where the handling of this case guided by the law court for custody of children and children separated from adult. But in fact they are combined whit adult, this is violate certainly the rights of the child set out in te child protection laws.Problem in this study are forms of effense stipulated in legislation narcotics, what are the rights of the investigation and what polise authority according to police law. The purpose of this research is to implement chikdren’s rights in the level of the police investigation in order not equate whit the reality of this adult. This type of research is sociological research, is research of secondary date to then proceed whit the study of primary data in the field. Or in a accordance with the fact that life in society to complete the data conducted interviews whit the perpetrators of criminal. In this care Anggi Fernando and Wella Hasan as well as parents actors and also the invesgtigator and head of the detective service unit director of the regional police drug Riau. And the data source is primary data and secondary consist of primary legal materials, and secondary and tertiary legal materials. Then the data were analyzed descriptively that analyzed data obtained from the filed and guided by legislation.In this study concluded that in the handling of criminal cases commited by children narcotics still. Not in accordance with laws and regulation. Where one as prisoners to custody for the child is still combine with adult prisoners there fore. The authors suggest the construction of a special child cus to dy rights in order to run as laws.Keywords: Investigation-Narcotics-Children